La aplicablidad de la ley orgánica del Sistema Nacional de Contratación Pública y su influencia en la validéz procesal jurídica, en los procedimietos planificados por la EERSA, durante el año 2011. - Zárate Lluguín, Verónica Mariela (2015)
The Public procurement can be defined as the electronic way that public administration has found in order to make all kinds of recruitment, it means the acquisition of goods or hiring a service. Nowadays the national service procurement of Ecuador is responsible for implementing the rules governing this branch, being the contracting entities (usually public sector entities or possess State income entities) and the providers those who wish to contract with the State, who must comply with these regulations. The research project entitled “ THE APPLICABILITY OF THE ORGANIC LAW OF NATIONAL PUBLIC PROCUREMENT SYSTEM AND ITS INFLUENCE ON THE LEGAL PROCEDURE VALID IN THE PLANNED PROCEDURES by the EERSA during the period 2011 in addition to actual information technical surveys were used as the administrative staff and suppliers of the EERSA and such compiled information the analysis was performed where it is detected that said institution, effectively apply framed by the normative matter rules in each of these recruitment procedures planned, at the beginning of the year in their annual procurement Plan. The results get of the discussion has allowed evaluated which served in this research to expose conclusions and final recommendations